Design and Development of a Compact Automated Parking System: Integration of Vertical Rotary Mechanism and IoT Interface - Md. Mehedi Hasan; Ismail Hossain; Mumit Hassan; Monowar Wadud Hridoy (Engineering Reports)
ABSTRACT The swift expansion of cities and the surging proliferation of vehicles have precipitated a severe scarcity of parking spaces all over the world. This predicament is aggravated by the spatial limitations of densely populated urban areas. Therefore, this study seeks to address the pressing need for efficient space utilization by introducing a compact automated parking solution. Given the glaring inadequacy of parking spaces relative to the soaring number of cars, this paper meticulously details the design and development of a Compact Automated Parking System (CAPS). The system utilizes a vertical‐rotary mechanism to maximize spatial efficiency while maintaining structural integrity. A fully functional prototype has been seamlessly incorporated with Internet of Things (IoT) technology. IoT enables real‐time monitoring of parking availability. The integration of the Blynk platform ensures an intuitive user interface. The proposed CAPS operates via an Arduino‐based control system, synchronized with sensors and actuators to execute precise motor movements and platform alignment. Although it is a basic control setup, it effectively demonstrates automation and synchronization in a compact prototype. System performance was assessed through time efficiency and user experience metrics, yielding favorable outcomes. Comparative analysis with conventional parking solutions highlights its superior efficiency. A scalable solution is also offered to consider this prototype for real‐world implementation. The fusion of automated vertical‐rotary mechanics and IoT distinguishes this system from existing alternatives. Ultimately, this innovation heralds a transformative shift in urban parking paradigms.